CC-223, NSC781406, and BGT226 Exerts a Cytotoxic Effect Against Pancreatic Cancer Cells via mTOR Signaling - Guo, Yangyang; Zhu, Hengyue; Weng, Min; Zhang, Hewei; Wang, Cheng; Sun, Linxiao (Frontiers in Pharmacology, 2020)
The mTOR signaling pathway is abnormally activated in pancreatic cancer and is related to tumor glucose metabolism. However, its specific regulation mechanism is still unclear. Therefore, this study aims to investigate whether Sestrin2 affects the glucose metabolism of pancreatic cancer by modulating mTOR signal and then affects its biological behavior. We have observed that L-leucine can promote the proliferation of pancreatic cancer cells and increase the expression of Sestrin2 and p-mTOR proteins. In order to further study the role of Sestrin2 and mTOR signaling in pancreatic cancer, we conducted Sestrin2 overexpression and mTOR pharmacological inhibition experiments. We found that Sestrin2 overexpression can increase glycolysis of pancreatic cancer cells and promote their proliferation. This effect can be eliminated by mTOR inhibitors. Finally, we found that Sestrin2 knockdown could inhibit the growth of pancreatic cancer in vivo. In conclusion, these findings suggest that Sestrin2 may promote the occurrence and development of pancreatic cancer through mTOR signaling.